Status of Agroforestry in Rice-based Mixed Farming Systems in Northen and Southern Bangladesh - Hoque, Ziaul; Ahmen, Minhaz; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2024)
With the collaboration of International Rice Research Institute (IRRI), the activity was conducted across two major regions: the northern region, encompassing the districts of Rangpur and Nilphamari, and the southern region, focusing on the districts of Patuakhali and Barguna. The activity aimed to evaluate the current status of agroforestry practices, farmers' perceptions and willingness to adopt rice-based mixed agroforestry practices and analyze land use and land cover (LULC) changes over time to inform future agricultural strategies.